A NEW STATUS FOR DESMODIUM OVALIFOLIUM (PAPILIONACEAE) - RUGAYAH RUGAYAH (REINWARDTIA, 1987)
Based on differences in anatomical and morphological characters, the new combination Desmodium heterocarpon (L.) DC. subsp. heterocarpon var. ovalifolium (Wall, ex Prain) Rugayah is proposed to accommodate some specimens formerly included in D. heterocarpon var. heterocarpon,